EFFECTIVENESS OF SPLINTING STRUCTURES MADE OF THERMOPLASTIC POLYMERS AND COBALT-CHROMIUM ALLOY IN THE TREATMENT OF PERIODONTAL DISEASES (World Bulletin of Public Health, 2026)
The article is devoted to the study of the mechanical properties and effectiveness of splinting structures made of the thermoplastic polymer Vitacryl and cobalt-chromium alloy in the treatment of periodontitis